FLAMING CELLS DI MULTIPLE MYELOMA - Nursin Abd. Kadir; Hj. Darmawaty E.R,; Mansyur Arif (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2010)
Multiple myeloma is a type of cancer on plasma cells which are system of immune cells in bone marrow that produce antibodies. A47 years old man precented with an excruciatingly painfull bone lytic lesion acompanied with compressive fracture in his Thorakal XIIand first Lumbar vertebral body since a week ago. A complete blood count on admission showed anemia normocytic normocrom withhemoglobin content of 5.3 mg/dL. The blood smear revealed clumping of red blood cells to bound "Rouleaux formations". Serum proteinelectrophoresis showed specific evidence of a M-spike. Bence-Jones proteinuria was positive and serum kreatinin arised 2.44 mg/dL.The bone marrow aspiration contained 45% plasma cells, many of which exhibited the morphology of flaming cells with an eccentricnucleus and violaceous cytoplasm. Plasma cells varied in size and shape and included flaming cells and myeloma cells. The patient wasdiagnosed as having flaming cells in multiple myeloma stage IIIB.